2013
DOI: 10.1108/nfs-04-2012-0037
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and socio-economic status in Greek adolescents

Abstract: Purpose -The study aims to explore the effect of socio-economic status (SES) on energy balance behaviours and adherence to the Mediterranean diet (MD), in Greek adolescents. Design/methodology/approach -391 students, 14-16 years old, have been recruited from two public high schools located in low SES areas of Athens and two private high schools from higher SES areas. Students completed a specifically designed energy balance behaviours questionnaire together with the Physical Activity Questionnaire for Adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…Regarding the family economic status and its association with the children's level of adherence to the Mediterranean diet, it is presented that there was no significant association between these two variables. This result is not expected as several other study attained different outcomes and found that there is a significant relationship between them (20,21).…”
Section: Discussioncontrasting
confidence: 65%
“…Regarding the family economic status and its association with the children's level of adherence to the Mediterranean diet, it is presented that there was no significant association between these two variables. This result is not expected as several other study attained different outcomes and found that there is a significant relationship between them (20,21).…”
Section: Discussioncontrasting
confidence: 65%
“…Ten articles reported on changes in mealtime behaviours after a crisis: five during COVID-19 (Ammar et al , 2020; Ben Hassen et al , 2020; Carroll et al , 2020; Romeo-Arroyo et al , 2020; Sidor and Rzymski, 2020), four during an economic recession (Bruening et al , 2012; Carney, 2012; Costarelli et al , 2013; Purdam et al , 2016) and one in the aftermath of Hurricane Katrina (Harvey, 2017). The mealtime behaviours found in this review were number of meals eaten, frequency of meals and whom meals were eaten with.…”
Section: Resultsmentioning
confidence: 99%
“…Dietary pattern changes is discussed in 31 articles: 15 focused on COVID-19 (Adams et al , 2020; Ammar et al , 2020; Ben Hassen et al , 2020; Carroll et al , 2020; Castellini et al , 2020; Di Renzo et al , 2020; Górnicka et al , 2020; Laguna et al , 2020; Papandreou et al , 2020; Pellegrini et al , 2020; Phillipou et al , 2020; Romeo-Arroyo et al , 2020; Ruiz-Roso et al , 2020; Scarmozzino and Visioli, 2020; Sidor and Rzymski, 2020), 8 focused on natural disasters (Carmassi et al , 2015; Cunsolo Willox et al , 2012; Forbes, 2017; Friel et al , 2014; Kuijer and Boyce, 2012; Larrance et al , 2007; Ma et al , 2020; Turner-McGrievy et al , 2020), 7 focused on economic recession (Alves and Perelman, 2019; Bonaccio et al , 2014; Bruening et al , 2012; Carney, 2012; Costarelli et al , 2013; Dore et al , 2003; Dowler and Lambie-Mumford, 2015) and 1 focussed on terrorism (Spillman, 2003). All articles, except for one, found that crisis did have an impact on the population’s dietary pattern.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations